TINGKAT PEMAHAMAN GURU TERHADAP PENERAPAN KURIKULUM MERDEKA DI SMPN 10 PONTIANAK - Imelda, Imelda; Seli, Sesilia; Wartiningsih, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This research aims to determine the level of teachers' understanding of the independent curriculum policy at SMPN 10 Pontianak. The research method used is a descriptive method to describe the level of teacher understanding of the implementation of the independent curriculum, using the form of quantitative research. The sample for this research was 35 teachers at SMPN 10 Pontianak. The data collection technique used was a questionnaire. The data analysis technique used in this research is descriptive statistics. The results of this research indicate that there is a level of teacher understanding of the independent curriculum policy at SMPN 10 Pontianak. The results of this research indicate that: (1) the level of teacher understanding of curriculum documents is not significant because the statistical test result of 0.133 is greater than the significance level of 0.005; (2) the level of teacher understanding of the teaching module is significant because the statistical test result of 0.001 is smaller than the significance level of 0.005; (3) the level of teacher understanding of the application of teaching modules is significant because the statistical test results are greater at 0.003, smaller than the significance level of 0.005. The average value of the results of the level of teacher understanding of the independent curriculum policy at SMPN 10 Pontianak is in the high category of 33.3%, which is 12 teachers, the medium category is 39.96%, which is 14 teachers, and the low category is 26.64% which is totaling 9 teachers.